2015
DOI: 10.1080/17445647.2015.1088751
|View full text |Cite
|
Sign up to set email alerts
|

Recreational trails in the Poprad Landscape Park, Poland: the spatial pattern of trail impacts and use-related, environmental, and managerial factors

Abstract: Multiple maps at a scale of 1:51,500, portraying the trail-related features of 43.4 km of recreational trails located in a mountainous area of the Poprad Landscape Park (south-central Poland), were produced. More specifically, the maps presented the spatial pattern of trail impacts (i.e. trail width; trail incision; the number of informal trails; old, abandoned trail sections; a presence of muddy sections and water puddles), as well as use-related (type and amount of use), environmental (vegetation type, densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…These landscape areas do not truly belong to the part of the trail that goes through the valley, where the landscape is composed of a green area with trees on its sides. This seems not to be in agreement with findings from other studies, which point to the presence of trees as a determinant factor for capturing the attention of the hiker [ 12 , 25 ]. Nevertheless, as affirmed by Chhetri et al [ 15 ] and Ried et al [ 36 ], the perception of the landscape is a complex cognitive construction, in which the hiker will constantly change his or her evaluation of the scenic beauty throughout the hike as a result of the different attributes that comprise the scene.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…These landscape areas do not truly belong to the part of the trail that goes through the valley, where the landscape is composed of a green area with trees on its sides. This seems not to be in agreement with findings from other studies, which point to the presence of trees as a determinant factor for capturing the attention of the hiker [ 12 , 25 ]. Nevertheless, as affirmed by Chhetri et al [ 15 ] and Ried et al [ 36 ], the perception of the landscape is a complex cognitive construction, in which the hiker will constantly change his or her evaluation of the scenic beauty throughout the hike as a result of the different attributes that comprise the scene.…”
Section: Discussioncontrasting
confidence: 94%
“…The increasing popularity of hiking has led scientific research to focus its attention on the study of the existing differences in the spatiotemporal flow of the hikers [ 1 , 7 , 13 , 14 , 15 , 16 , 21 , 22 , 23 ]. Thus, it is observed that hikers themselves, as well as the surroundings where the sport is practiced, have become priorities in scientific research [ 1 , 4 , 18 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the scale at which recreation occurs should also be considered (Graham & Eigenbrod, 2019;Zhukov et al, 2019). The recreational trails are an important aspect of the impact on the soil (Ballantyne & Pickering, 2015;Huang et al, 2015;Tomczyk & Ewertowski, 2016). Such impact is associated with compaction of the soil (Azlin & Philip, 2004;Ballantyne & Pickering, 2015), an increase in soil penetration resistance (Landsberg et al, 2003;Campbell et al, 2013), changes in the soil aggregate structure (Bird et al, 2007;Fattet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A review of previous work revealed several related research themes, which informed our study. For instance, a limited number of studies have used a geographic information system (GIS) to examine recreation use or impacts at the scale of protected areas (eg Arrowsmith and Inbakaran 2002;Hawes et al 2013;Tomczyk and Ewertowski 2016). These studies have generally focused on vegetation disturbance, soil loss, and trail impacts.…”
Section: Wildland Recreation Disturbancementioning
confidence: 99%